Feminism and the Changing of Sociological Perspectives on Women - Siregar, Wahidah Zein Br (The Sociology of Islam, 2021)
Women are part of society. Therefore, it is a precondition that they become part of discussions in sociology. How does this discipline see women? This paper aims to respond to two research questions: How did sociologists, particularly in the classic era, talk about women? What is influence of feminism to the study on women in sociology? To answer these two questions, I conduct a library research by reading and analyzing literatures relevant to the topic. Some aspects that become my attention are the perspectives of classic sociologists on women, respond of feminists to them, and changes that happen in sociology as the result of those feminists’ challenges. My reading on those literatures shows that in its early development, sociologists perceived women as inferior individuals in society. Feminism, in particular the second wave of feminism brings significant influences to those views. Sociology at present time places women in more egalitarian position. Studies on women in sociology also develop significantly.